Variation patterns in natural populations of wild potatoes along Quebrada de Inca Cueva, northwestern Argentina - Ispizua, Veronica Nilda; Camadro, Elsa Lucila; Clausen, Andrea Martina (Springer, 2019)
Wild potato species, Solanum infundibuliforme Phil. (ifd) (2n = 2x = 24), S. gourlayi Hawkes (grl) (2n = 4x = 48) and presumed grl–ifd hybrids (2n = 4x = 48) were collected from a narrow gorge known as Quebrada de Inca Cueva, located in Jujuy province, Argentina. To explore the possibility of gene flow and introgression within and between populations and ploidy levels, accessions collected in this gorge and others from neighboring valleys, identified as Solanum oplocense Hawkes (opl), grl and ifd, were characterized according to chromosome number, morphological characters, pollen–pistil relations and seed set following controlled diallelic crosses. Multivariate analysis for 36 morphological characters recorded in individual plants revealed considerable variability. Principal coordinates analysis, revealed that tetraploid populations belonging to presumed hybrids and grl formed a huge swarm in which individuals from different populations appeared intermixed. In one accession (ClI 1715), variation in morphological phenotypes in diploid and tetraploids plants were detected, as well as individuals with intermediate characters between the putative parents. The crossing results revealed the action of postzygotic barriers between ifd and presumed hybrids as well as between ifd–opl and grl–opl. These barriers were incomplete as normal seeds were obtained in certain genotypic combinations. In intraspecific crosses and grl × presumed hybrids crosses, pollen tubes grew normally to the base of the style producing fruits with a variable number of seeds in each. The breeding strategy of these species has resulted in complex mixtures of parental genotypes, advanced hybrid generations and backcrosses in this gorge. The implications of these results for germplasm conservation are discussed.